A MODEL OF ISLAMIC PUBLIC FINANCE IN MALAYSIA’S CONSTITUTION - Abdul Ghafar Ismail (Fakultas Hukum, Universitas Diponegoro, 2021)
This study asks five questions. How does the Constitution define the framework for its governance and the principles under which it must operate? How do the provisions lay out the core public finance matters? How are Islamic religious defined? How could we interpret the provisions in the Constitution? How do Islamic religious revenues affect socioeconomic development? Based on the analysis of these questions, and the Federal Constitution of Malaysia, this study will try to explain the choice of alternative sets of legal-institutional-constitutional rules that constrain the choices and activities of economic and political agents (government). In particular, this study will prove that the Constitution results from both conventional and Islamic scholars' preferences. The constitutional rules lead to the introduction of Islamic religious revenues as the sources of government revenues. Furthermore, in Malaysia, constitutional economics also provides another view that treats Islamic religious revenues as socioeconomic development tools.